Bullying Pada Remaja di Kota Tanjungpinang - Estariani Iskandar; Emmy Solina; Marisa Elsera (CV Insan Kreasi Media, 2022)
This research discusses Bullying on teenage in Cities Tanjungpinang. This research looked at the phenomenon of Bullying that occurs in adolescent. The bullying referred to in the research to in the study is verbal Bullying. Verbal Bullying is a from of Bullying that is carried out like insulting, mocking, the presence of threats and untrue accusations that can be done with respect to continuous casualties. The purpose of this research is to explain how bullying happens to teenagers in Tanjungpinang City and explains about the impact of bullying on victims. This research used this type of qualitative approach research, with the determination of informants bye means of purposive sampling, this research took as many as 8 informants who based on considered to be able to answer information that needed by researchers. With data collection techniques using observation, interviews, and documentation. In this study used Anomie theory of Emile Durkheim. The results of this study concluded that in this study victims of bullying who experienced cases of bullying victims did not feel the perceived impact of bullying and there were some victims who felt the impact of verbal bullying.